The Effectiveness of Pulmonary Rehabilitation in COVID-19 Patients - Putu Diva Dharma Suta; Dedi Silakarma (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Patients with COVID-19 have experienced numerous symptoms prior to and after hospitalization, particularly in the respiratory system. The symptoms vary widely. Based on symptoms occurring through patients’ airways, most patients who have recovered from COVID-19 still have enduring symptoms of breathlessness. Pulmonary rehabilitation can be an option of rehabilitation programs directed to the patients. Aim: Explore the effectiveness of pulmonary rehabilitation specifically in COVID-19 patients. This literature review seeks to provide an agenda for further research related to adjusted treatment on pulmonary rehabilitation based on the patients’ needs. Material and Methods: The author synthesized, reviewed, and analyzed 10 literatures employing semi-systematic review technique. Results: The short-term aim of pulmonary rehabilitation is to reduce dyspnea and anxiety as well as depression, meanwhile the long-term aim is to maintain patients’ functional status to the maximum extent, improve quality of life and facilitate patients to return to performing daily activities. In addition, a 6-minute walking test and sit-to-stand test might be the alternative exercise to improve respiratory functions. Conclusion: Pulmonary rehabilitation should be provided during the treatment process, including inpatients or outpatients phase to ensure returning patients’ recovery of respiratory function. Moreover, exercise recommendations should be tailored based on patients’ specific needs.